KARAKTERISASI DAN STUDI STABILISASI a-AMILASE Bacillus licheniformis TVII.6 MENGGUNAKAN BAHAN ADITIF - Puji Lestari; Nur Richana; Rosmimik Rosmimik (BERITA BIOLOGI, 2011)
The limited stability of enzyme during long-term storage attributes to its reduced function. In this study, a-amylase from Bacillus licheniformis TVII.6 were formulated with different kind of additives for storage stabilization and better performance. Simultaniously, some minerals and calcium ion were applied to elucidate the inhibition and activation effects to a-amylase. Crude enzyme which was prepared by aceton precipitation was used for this stability test. It demosntrated that 10% of mannitol in citrate phosphate buffer gave the highest residual activity after 3 months of storage (98.5%). Calcium ion influenced the thermal stability of a-amylase and it gave optimum activity at 5 mM CaCl , thus the stability increased from 76.0%/90 C/2 hours to 114.8%/90 C/22 hours in comparison without calcium ions. Calcium ions (5 mM CaCl ) on the stability of a-amylase at 4 C also produced the 2highest residual activity, which remained 100% during 48 hours of incubation. Chemical compounds like FeSO , Na CO and EDTA 4 2 3acted as inhibitors, while (NH ) SO , CuSO , CoSO , MgCl and K HPO did not inhibit activity of a-amylase. NaOH and MnCl 4 2 4 4 4 2 2 4 2 compounds at low concentrations (2 mM) did not inhibit the enzyme but at 10 mM became a-amylase inhibitors. This amylase stability information is very important as a consideration when applying and storing the enzyme, thereby reducing the degradation a-amylase activity.